El fin de una era: Pío IX y el Syllabus - Cárdenas Ayala, Elisa (El Colegio de México, A.C., 2015)
This article aims to show how Pius X and his most famous document, the Syllabus of Errors, published in 1864, participated in the end of a centuries-old era in the history of Catholicism that was characterized by the existence of the temporal dominion of the Popes, close ties between the Catholic Church and monarchism as a form of government and the conception of the Catholic faith as the only road to salvation. This was the end of an era, not just from the perspective of the power of institutions, but also in terms of the representations that accompanied them. The article is supported by a Braudelian analysis of the times in which the Pope and his document belonged and makes use of the categories proposed by R. Koselleck for the study of the experience of time.